Quantitative nanohistological investigation of scleroderma: an atomic force microscopy-based approach to disease characterization - Strange AP (Dove Medical Press, 2017)
Adam P Strange,1 Sebastian Aguayo,1 Tarek Ahmed,1 Nicola Mordan,1 Richard Stratton,2 Stephen R Porter,3 Susan Parekh,4 Laurent Bozec1 1Department of Biomaterials and Tissue Engineering, UCL Eastman Dental Institute, 2Centre for Rheumatology and Connective Tissue Diseases, Royal Free Hospital, UCL Medical School, 3UCL Eastman Dental Institute, 4Department of Pediatrics, UCL Eastman Dental Institute, London, UK Abstract: Scleroderma (or systemic sclerosis, SSc) is a disease caused by excess crosslinking of collagen. The skin stiffens and becomes painful, while internally, organ function can be compromised by the less elastic collagen. Diagnosis of SSc is often only possible in advanced cases by which treatment time is limited. A more detailed analysis of SSc may provide better future treatment options and information of disease progression. Recently, the histological stain picrosirius red showing collagen register has been combined with atomic force microscopy (AFM) to study SSc. Skin from healthy individuals and SSc patients was biopsied, stained and studied using AFM. By investigating the crosslinking of collagen at a smaller hierarchical stage, the effects of SSc were more pronounced. Changes in morphology and Young’s elastic modulus were observed and quantified; giving rise to a novel technique, we have termed “quantitative nanohistology”. An increase in nanoscale stiffness in the collagen for SSc compared with healthy individuals was seen by a significant increase in the Young’s modulus profile for the collagen. These markers of stiffer collagen in SSc are similar to the symptoms experienced by patients, giving additional hope that in the future, nanohistology using AFM can be readily applied as a clinical tool, providing detailed information of the state of collagen. Keywords: rheumatology, adjunct diagnosis, picrosirius red, collagen, nanohistology